Pengembangan Kompetensi Pemasaran Digital bagi Wirausaha Kelompok Buruh Migran dan Keluarganya - Narida, Marshelia; Angel Damayanti; Leonard Hutabarat; Andaru Satnyoto; Alif Oktavian; Iyan Septiyana (LPPM Stikosa - AWS, 2024)
The Indonesian Migrant Workers Union (SBMI) is an organization that represents the interests of Indonesian migrant workers. SBMI aims to advocate for the rights of migrant workers in Indonesia, protect them from exploitation, and improve their working conditions and welfare. Through the learning and development of accounting systems, promotion management, digital marketing, and innovative product development for digital-based economic groups, the Indonesian Migrant Workers Union (SBMI) is expected to provide a good opportunity to enhance personal and family economics. The Community Service Team (PkM) from Fisipol UKI collaborated with lecturers from Pasundan University to initiate the socialization and training for migrant worker unions in Sukabumi, West Java. The PkM team focused on training participants in utilizing E-Commerce applications and the Tik-Tok social media application to market their products. Participants also engaged in direct practice of marketing products on E-Commerce and Tik-Tok applications. After undergoing direct training, participants then completed a post-test, showing significant progress with 97% of participants understanding the concept of marketing using E-Commerce and Tik-Tok. At the conclusion of the socialization and training, the UKI PkM Team provided social media accounts and phone numbers to participants for easier communication when they have questions or need assistance with product marketing.